2015
DOI: 10.1016/j.apsusc.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Growth and surface modification of LaFeO3 thin films induced by reductive annealing

Abstract: a b s t r a c tThe mixed electronic and ionic conductivity of perovskite oxides has enabled their use in diverse applications such as automotive exhaust catalysts, solid oxide fuel cell cathodes, and visible light photocatalysts. The redox chemistry at the surface of perovskite oxides is largely dependent on the oxidation state of the metal cations as well as the oxide surface stoichiometry. In this study, LaFeO 3 (LFO) thin films grown on yttria-stabilized zirconia (YSZ) was characterized using both bulk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The difference of spin-orbit splitting between La 3d 5/2 and La 3d 3/2 is about 16.8 eV, which is in accordance with the previous report [30]. The line of the La 3d core-level revealed that the La primarily shows a valence state of +3 [29]. The XPS spectra further confirms the prepared nanoparticles to be stoichiometric LaFeO 3 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The difference of spin-orbit splitting between La 3d 5/2 and La 3d 3/2 is about 16.8 eV, which is in accordance with the previous report [30]. The line of the La 3d core-level revealed that the La primarily shows a valence state of +3 [29]. The XPS spectra further confirms the prepared nanoparticles to be stoichiometric LaFeO 3 .…”
Section: Resultssupporting
confidence: 90%
“…The signal of carbon can be attributed to the residual carbon on the surface of the sample. It can be observed from Figure 3c that the peaks located at 724.4 eV and 710.6 eV are attributed to the binding energies of Fe 2p1/2 and 2p3/2, respectively [29]. It is notable that shoulder peaks didn't appear in the Fe 2p spectra, which means that Fe primarily shows +3 oxidation state.…”
Section: Resultsmentioning
confidence: 93%
“…For LaO-LFO, a third peak is present at ~2.3 eV higher binding energy, termed "surf". Such a surface feature has been often observed for epitaxial perovskite films of unknown termination, as well as perovskite particles, and has been attributed to a host of potential species such as carbonates, 29,30 adsorbed water, 31,32 hydroxyls, [31][32][33] peroxide species, 34 undercoordinated oxygen, 35,36 and the terminal layer(s) of a polar surface due to a shift in Madelung potential. 17 Considering the AP-XPS spectra collected at 300 °C in 100 mTorr oxygen (and similarly at ~24 mTorr oxygen, Figure S4), we rule out the presence of carbonates and adsorbed water, and the lack of such a feature on the FeO 2 -terminated surface suggests it does not arise from a change in Madelung potential at the surface.…”
mentioning
confidence: 99%
“…For example, it is common in the literature to associate a higher binding energy peak 2.3 eV above the metal oxide binding energy with oxygen vacancies, but the origin of this peak is the subject of some controversy and it can easily be due to other surface chemistry effects that will confuse the analysis. 79,82…”
Section: Oxide Surface Chemistrymentioning
confidence: 99%